The Adipo-Fascial ALT Flap in Lower Extremities Reconstruction Gustillo IIIC-B Fractures. An Osteogenic Inducer?. Issue 6 (3rd July 2021) - Cherubino, Mario; Corno, Martina; Ronga, Mario; Riva, Giacomo; di Summa, Pietro G.; Sallam, Davide; Tamborini, Federico; Maggiulli, Francesca; Surace, Michele; Valdatta, Luigi
Abstract: Background : Purpose of this report is to analyze possible effects and clinical outcomes of anterolateral thigh (ALT)-free fascial flaps on bone healing in Gustilo type IIIB-C open tibial fractures. Methods : We present a technique, wherein the fascia is wrapped around bone stumps, bone chips or not vascularized bone graft were used to fill the defects. Five patients with a mean follow-up of 36 months were treated. Results: Mean time from injury to flap coverage was 72 hours. The mean size of bone defects was 4-7, 6 cm. All flaps were Antero Lateral Tight flaps, and the fracture sites did not have any evidence of infection. None of the patients was a smoker. A solid bone union was reached, and full wearing was in a mean of 11 (4–20) weeks after the injury. The lower limb was saved in 100% of the cases. Conclusion: Despite the goods results, further studies applied on a large number of patients are needed to confirm authors theory, however, we can consider the fascial ALT flap as a valid help for bone healing in 3B-C open tibial fractures.